Environmental performance and biophysical constrains of Italian agriculture across time and space scales - Zucaro, Amalia; Mellino, Salvatore; Ghisellini, Patrizia; Viglia, Silvio (Journal of Environmental Accounting and Management, 2026)
This paper evaluates the resource use and environmental performance of the Italian agricultural sector across levels, from local (selected olive, lemon and grape farms), through regional (Campania region) up to the national scale (whole Italy). An assessment over time (from 1985 to 2010) was performed in order to investigate how the demand for environmental support changed in the last twenty-five years. The performance indicators were calculated by using the Emergy Synthesis method in order to ascertain the emergy investment per unit of product (dry-mass, available energy, monetary value) as well as the overall sustainability of the process. Results point out both a decrease of renewability (%REN) and a higher dependence from imported resources (high Environmental Loading Ratio, ELR and low Emergy Yield Ratio, EYR) at all the scales investigated. The main factors affecting such indicators are the choice of crops mix, machinery use, climate conditions (mainly rainfall), market value of products, direct and indirect labor. A scenario analysis was implemented based on increased resource use efficiency in order to assess the sustainability improvement potential of the agricultural system.